Amyloid-beta deposition is associated with increased medial temporal lobe activation during memory encoding in the cognitively normal elderly - Edelman, Kathryn (Am J Geriatr Psychiatry, 2017)
BACKGROUND: Much is unknown about changes that occur in the brain in the years preceding the cognitive and functional impairment associated with Alzheimer’s disease (AD). This period before mild cognitive impairment is present has been referred to as preclinical AD, and is thought to begin with amyloid-beta deposition and then progress to neurodegeneration and functional brain circuit alterations. Prior studies have shown that there is increased medial temporal lobe activation on functional magnetic resonance imaging (fMRI) early in the course of mild cognitive impairment. However, it is unknown whether this altered fMRI activity precedes cognitive impairment. The purpose of this study is to address this question using Pittsburgh Compound-B (PiB) imaging and fMRI in a sample of cognitively normal older adults. METHODS: Forty-four cognitively normal older adults underwent both PiB imaging and fMRI with a face-name memory task: 21 were classified as PiB(+) and 23 were PiB(−). Additionally, thorough cognitive and neuropsychological test batteries were administered outside the scanner. The main outcome measure in this study is fMRI activation in the medial temporal lobe during a face-name memory-encoding task. RESULTS: PiB(+) subjects showed higher fMRI activation during the memory task in the hippocampus relative to PiB(−) participants. CONCLUSIONS: The increased medial temporal lobe activation in preclinical Alzheimer’s disease, observed in this study, may serve as an early biomarker of neurodegeneration. Future studies are needed to clarify whether this functional biomarker can stratify Alzheimer’s Disease risk among PiB(+) older adults.